网络远程招生方式前后三年脑血管病方向统招硕士研究生生源情况分析 Analysis of the Source of Master Students in Cerebrovascular Disease Direction in Three Years before and after Online Remote Enrollment - 杜鑫，张家亮，霍墨菲(DU Xin, ZHANG Jialiang, HUO Mofei ) (Zhongguo cuzhong zazhi, 2024)
目的 通过对比网络远程招生与非网络远程招生方式下脑血管病方向统招硕士研究生的一般情况和成绩等信息，探讨网络远程招生方式对生源质量的影响。 方法 以首都医科大学附属北京天坛医院2017—2022年脑血管病方向的统招硕士研究生为研究对象，根据招生方式将其分为两组，2017—2019年招收的统招硕士研究生为非网络远程招生组，2020—2022年招收的为网络远程招生组。本研究主要通过历年的研究生复试名单来获取研究数据，收集的信息包括考生的性别、年龄、民族、毕业院校、是否是应届生等基本信息以及其初试成绩和复试成绩，并对两组考生的上述指标进行差异化分析。 结果 2017—2022年，首都医科大学附属北京天坛医院脑血管病方向的统招硕士研究生生源数量总体呈增长趋势。在所招收的统招硕士研究生中，女性88名（33.98%），比例低于男性，民族以汉族（246名，94.98%）为主，来源以应届毕业生（203名，78.38%）为主，网络远程招生组与非网络远程招生组相比，上述指标的差异均不具有统计学意义。网络远程招生组生源的平均年龄显著小于非网络远程招生组[（23.1±1.1）岁 vs.（23.5±1.3）岁，P=0.014]。网络远程招生组神经病学和外科学（神经外科）专业的统招硕士研究生复试成绩均显著高于非网络远程招生组[神经病学，（255.5±12.3）分 vs.（241.0±13.8）分，P<0.001；外科学（神经外科），（259.9±11.6）分 vs.（249.3±13.1）分，P<0.001]。 结论 网络远程招生的硕士研究生复试成绩在一定程度上优于非网络远程招生，为未来研究生招生形式提供了参考。 Abstract: Objective By comparing the general situation and examination results of the master students in the field of cerebrovascular diseases between online remote enrollment and non-online remote enrollment, this paper discusses the influence of online remote enrollment on the quality of students. Methods The subjects of this study were the master students of cerebrovascular diseases in Beijing Tiantan Hospital, Capital Medical University from 2017 to 2022. According to the enrollment method, the master students enrolled from 2017 to 2019 are the non-online remote enrollment group, and the students enrolled from 2020 to 2022 are the online remote enrollment group. This study obtains research data through the list of reexaminations over the years, and collects basic information such as gender, age, ethnicity, graduated university, whether it is a fresh graduate, as well as preliminary examination results and reexamination results. The above indexes of the two groups are analyzed differently. Results From 2017 to 2022, the number of master students in the direction of cerebrovascular diseases in Beijing Tiantan Hospital, Capital Medical University showed an overall growth trend. Among the enrolled master students, 88 are female, accounting for 33.98%, the proportion is lower than that of males. The ethnic group is mainly Han (246, 94.98%), and the source is mainly fresh graduates (203, 78.38%). The differences of the above indexes were not statistically significant between the online remote enrollment group and the non-online remote enrollment group. The mean age of online remote enrollment group was significantly lower than that of non-online remote enrollment group [(23.1±1.1) years vs. (23.5±1.3) years, P=0.014]. The reexamination results of the master students majoring in neurology and surgery (neurosurgery) in the online remote enrollment group were significantly higher than those in the non-online remote enrollment group [neurology, (255.5±12.3) points vs. (241.0±13.8) points, P<0.001; surgery (neurosurgery), (259.9±11.6) points vs. (249.3±13.1) points, P<0.001]. Conclusions The reexamination results of online remote enrollment are better than those of non-online remote enrollment to some extent, which provides a reference for future graduate enrollment method.